PENGARUH KEBIJAKAN DIVIDEN, KEBIJAKAN HUTANG DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN MANUFAKTUR - Krisnawati, Eka; Miftah, Munasiron (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2015)
This study aimed to examine the effect of Dividend Policy, Policy Liabilities and Profitability of Company Value of the companies listed in Indonesia Stock Exchange period 2011 to 2014. The population in this study a number of 60 companies listed in Indonesia Stock Exchange. Data obtained from financial statements 2011 to 2014 that has been published. Obtained a total sample of 15 companies. The analysis technique used is multiple linear regression and hypothesis testing with constant 5%.In this study occur existing data were not normally distributed, this is due to some extreme values that look very different from the value of other observations. Of the 60 samples of existing research, as many as 24 sample company data should be eliminated (outlier data). It is intended to dispose of the data extremes can cause data distribution becomes normal, so that the data is left as many as 36 samples were used.The results showed that the dividend policy has no significant effect on the value of the company, debt policy does not significantly influence the company's value and profitability significantly influence the value of the company. The coefficient of determination R square indicates 0,073 or 7,3% of explaining that the variable is explained by the variable company value and dividend policy, policy liability and profitability the remaining 92,7% is explained by other variables.